GIS MAPPING OF SOLID WASTE MANAGEMENT ALONG KM 0-77 CITARUM RIVER - Joku, Wayne (2015)
A great amount of information and analytical capacity is required when attempting to understand the co-dependency of the earth's ecosystems and human impact on the environment - and Geographic Information Systems (GIS) makes this a possible. No matter how large or small your community, planners must deal with spatial information. GIS is a tool that manages, analyzes, and models data from our environment so that we can make decisions based on that information to better control the impact humans have upon it. The spatial and thematic aspects of GIS technology enable users to overlay various data to outline and predict the future of our resources, land, water, plant life, and wildlife. Geoprocessing enables governments and conservation organizations alike to make intelligent decisions when implementing laws and programs that will protect and sustain the environment and its resources.